Individual long-term variation of platelet reactivity in patients with dual antiplatelet therapy after myocardial infarction: Results from Assessing Platelet Activity in Coronary Heart Disease (APACHE). (4th July 2019) - Alfredsson, Joakim; Swahn, Eva; Gustafsson, Kerstin M; Janzon, Magnus; Jonasson, Lena; Logander, Elisabeth; Nilsson, Lennart; Lindahl, Tomas L.
Abstract: There is a large inter-individual variation in response to clopidogrel treatment, and previous studies have indicated higher risk of thrombotic events in those with high residual platelet reactivity (HPR). Less is known about individual variation over time. The aim of this prospective cohort study was to investigate intra-individual variation in platelet reactivity. Platelet aggregation in whole blood was assessed in 77 patients, at 3 days, 8 days and 6 months after admission for acute myocardial infarction and loading dose of clopidogrel. All patients were treated with aspirin and clopidogrel through 6-month follow-up. We found a significant increase in median ADP-stimulated aggregation from third to eighth day (195 vs. 250 AU*min, p -value = 0.001) but not from day 8 to 6 months (250 vs. 223 AU*min, p -value = 0.666). There was no significant change in the overall rate of HPR (15.6% vs 20.8%, p -value 0.503) or low platelet reactivity (LPR) (37.7% vs 33.8%, p -value = 0.609) from day 8 to 6-month follow-up. In contrast, more than one in four changed HPR status, 15.6% from non-HPR to HPR and 10.4% HPR to non-HPR. A shift in LPR status appeared even more frequent, occurring in about one of three patients. In spite of similar median aggregation and rate of HPR during 6-month follow-up, about one in four of the patients changed HPR status and one in three changed LPR status. This may be important information for a concept of risk stratification based on a single aggregation value early after an acute coronary syndromes.